Relationship between Knowledge, Attitudes, and Practices of Universitas Mataram Students regarding the Use of Masks on the Occurrence of Maskne - Basyir, Ilma Fahira; Hidajat, Dedianto; Kusuma, Dinie Ramdhani (Universitas Islam Bandung, 2023)
Coronavirus disease 2019 (COVID-19) is transmitted from human to human and primarily via the respiratory route; hence, wearing a mask is the first step in preventing the spread of COVID-19. Behind the benefits of these masks are adverse consequences on the skin, such as lesions and acne. This study aims to ascertain the relationship between students' knowledge, attitudes, and practices regarding the use of masks on the occurrence of maskne. This research is a cross-sectional analytic observational study. The research subjects were 100 students from the Universitas Mataram's 2018 class, from November 2020 to January 2022, using a stratified random sampling technique—data collection from primary data via a Google Form. Data analysis was carried out by testing the lambda hypothesis. In this study, 38% (n=38) of the respondents reported maskne, while 62% (n=62) reported not maskne. Among the respondents who reported not maskne, the majority mentioned having good knowledge, positive attitudes, and good practice. The lambda hypothesis analysis indicates significant correlations between students' knowledge (p=0.004), attitudes (p=0.001), and practices (p=0.006) regarding mask usage and the occurrence of maskne. A relationship exists between students' knowledge, attitudes, and practices regarding mask usage and maskne occurrences.